Enlarged tibial eminence may be a protective factor of anterior cruciate ligament. (November 2020) - Li, Yujia; Chou, Ke; Zhu, Wei; Xiong, Jiepeng; Yu, Min
Abstract: Anterior cruciate ligament (ACL) is a primary stabilizer of the knee and constrains joint motion, and its injury is very common in clinic. There are many studies on the risk factors of ACL injury such as the ACL diameter, intercondylar notch width index (NWI), sagittal condylar shape, tibial posterior slope, tibia eminence size and so on. Large amount of research data has confirmed that all above are closely related to ACL injury. Among them the morphological characteristics of femoral condyle and tibial plateau are closely related to ACL injury. For example the tibial eminence, which is the hot topic of recent research. Whether or how does it relate to ACL injury has draw much interest of researchers. Since the tibial eminence and the ACL are both located in the intercondylar notch and adjacent to each other, we hypothesize the size of the tibial eminence may relate to the rupture of ACL. For there is report have found that reduced medial tibial eminence was associated with ACL injury, we suggest a hypothesis that enlarged tibia eminence may be a protective factor of ACL.